Leon Trotsky and Soviet Historiography of the Russian Revolution (1918–1931). Issue 2 (3rd July 2021) - White, James D.
Abstract : The article examines the part played by Leon Trotsky in establishing the principles on which Soviet historical writing on the Russian Revolution was carried on, including the practice of making programmatic versions of events universally obligatory. It also investigates the manner in which the respective remits of the two institutions, Istpart and the Institute of Red Professors (IKP), influenced the way the history of the 1917 revolution was presented in the 1920s. The article looks at how Istpart and IKP reacted to the anti-Trotsky campaign and at the debt Trotsky's History of the Russian Revolution owes to materials produced by the two institutions. It is in the light of the interaction of Trotsky's History and Soviet historiography that Stalin's 1931 letter to Proletarskaia revoliutsiia is to be understood.